Small steps - Sachar, Louis, 1954- (Delacorte Press, 2006)
Three years after being released from Camp Green Lake, Armpit is trying hard to keep his life on track, but when his old pal X-Ray shows up with a tempting plan to make some easy money scalping concert tickets, Armpit reluctantly goes along.